Regulatory focus and employee creativity: The role of individual participation and intellectual stimulation - Jovi Sulistiawan, - (Wolters Kluwer Medknow Publications, 2020)
The purpose of this study is to examine how regulatory focus, which consists of promotion and prevention, affects individual creativity and how the interaction effect between two contextual factors, intellectual stimulation and individual participation, will strengthen the effect of promotion focus to individual creativity. Employees in a radio stationwere used asour respondents with total 142 respondents. The authors tested the hypothesis by using hierarchical regression analysis and moderated regression analysis in order to test the moderating effect of intellectual stimulation and individual participation. The results of this study showed that promotion focus is positively related to creativity, whilst prevention focus is negatively related to creativity. Our interesting findings was only intellectual stimulation has a moderateeffect on promotion focus and creativity.